2010
DOI: 10.1016/j.ijpsycho.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Inter-hemispheric electroencephalography coherence analysis: Assessing brain activity during monotonous driving

Abstract: The current study investigated the effect of monotonous driving on inter-hemispheric electroencephalography (EEG) coherence. Twenty-four non-professional drivers were recruited to perform a fatigue instigating monotonous driving task while 30 channels of EEG were simultaneously recorded. The EEG recordings were then divided into 5 equal sections over the entire driving period for analysis. Inter-hemispheric coherence was computed from 5 homologous EEG electrode pairs (FP1-FP2, C3-C4, T7-T8, P7-P8, and O1-O2) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
(54 reference statements)
3
19
0
1
Order By: Relevance
“…Studies using spectral coherence also showed similar results during heightened fatigue [18], [19]. Significant increases of coherence values were observed in delta, theta, alpha, and beta bands [18] and the number of synchronized regions also increased [19]. In a study using spectral coherence and phase locking value (PLV), significant increases of PLV values in theta band occurred after a prolonged cognitive task, while PLV and spectral coherence values in beta band decreased significantly [22].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Studies using spectral coherence also showed similar results during heightened fatigue [18], [19]. Significant increases of coherence values were observed in delta, theta, alpha, and beta bands [18] and the number of synchronized regions also increased [19]. In a study using spectral coherence and phase locking value (PLV), significant increases of PLV values in theta band occurred after a prolonged cognitive task, while PLV and spectral coherence values in beta band decreased significantly [22].…”
Section: Introductionmentioning
confidence: 70%
“…Significant increases of mean phase coherence (MPC) in delta and alpha bands were observed during the period of driving drowsiness and the number of connective functional units (FUs) also increased [16]. Studies using spectral coherence also showed similar results during heightened fatigue [18], [19]. Significant increases of coherence values were observed in delta, theta, alpha, and beta bands [18] and the number of synchronized regions also increased [19].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Other authors have used different approaches to assess cerebral connectivity (David et al 2004;Stam 2005), and in this context cross-entropy measures have been proposed to characterize the probability of finding similar patterns between neural signals (Papadelis et al 2007;Zhang et al 2007;Xie et al 2010). Along with these innovative techniques, classical measures such as correlation, power spectral density and coherence have also been used recently (Franciotti et al 2006;Zavaglia et al 2008;Jap et al 2010;Alonso et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…During the transitional phase to fatigue, there were no significant differences in the delta and alpha magnitudes across the entire brain [9]. The inter-hemispheric EEG coherence analysis was shown in the study of Jap et al [10], which revealed that the interhemispheric coherence level was significantly higher at the frontal and occipital sites compared to the central, parietal, and temporal sites throughout the driving sessions.…”
Section: Changes In Eeg Signalsmentioning
confidence: 87%